FindCmd: A personalised command retrieval tool - Pengpeng Hou; Heng Zhang; Yanjun Wu; Jiageng Yu; Yuxia Miao; Yang Tai (IET Software)
Abstract The command line interface is a crucial way of interacting with Linux, many programs such as ls, pwd and netstat are used on it and it is also the primary way to access a server remotely. However, the command line interface is not user friendly and thus it is difficult to use; there are many programs and users do not know which one is appropriate for finishing their task. To help users find useful commands efficiently, the authors propose FindCmd that retrieves commands based on the local data and user familiarity with commands. Then the local command data are collected including user manual such as man, info and strings extracted from the binary ELF (executable and linkable format) file. Based on the characteristics of local data, an enhanced command retrieval framework is proposed. In addition, the authors marginally decreased the priority of familiar commands when retrieving commands since users tend to use command retrieval tool to find an unfamiliar command. To the best of our knowledge, this is the first local tool for personalised command retrieval. In the evaluation section, the authors compare FindCmd with retrieval tools apropos and howdoi; our experimental results show that FindCmd outperforms the other two tools in retrieving commands. In addition, the experiments demonstrate the effectiveness of personalised search of FindCmd.